CITA RASA KUDAPAN NUSANTARA DALAM NOVEL BERJUDUL NASGOR KARYA HARRY NAZARUDIN: KAJIAN GASTRONOMI SASTRA - Firmansyah, Ryan (Universitas Islam Malang, 2024)
Abstrak: Culinary is something that cannot be separated from human life. Likewise, literary works play an important role in human life. Literary gastronomy, also known as gastro criticism, is a combination of gastronomy and literary criticism. Gastronomy focuses on food and gourmet aspects, while literary criticism deals with the critical understanding of a literary work. The combination of the two creates a field of study or literary criticism that focuses on works that are rich in imagination in the context of culinary culture. This research method is descriptive qualitative with a gastro critical approach that aims to describe literary gastronomy in one of Indonesia's culinary specialties, namely fried rice. The research data consists of sentences and discourses from literary works as well as writings related to literary gastronomy, which are used as references in the analysis. Data collection techniques were conducted through close reading, while analysis was conducted using the Miles and Huberman model. The results show that the culinary aspects presented by the author include the origins, variants, processing materials, ways of serving and flavors of fried rice.